2022
DOI: 10.1111/sms.14148
|View full text |Cite
|
Sign up to set email alerts
|

Muscular heat shock protein response and muscle damage after semi‐professional football match

Abstract: Purpose: A typical football match leads to neuromuscular fatigue and physical performance impairments up to 72-96 h post-match. While muscle damage is thought to be a major factor, damage on the ultrastructural level has never been documented. The purpose of this study was to investigate post-match cellular muscle damage by quantifying the heat shock protein (HSP) response as a proxy for protein damage.Methods: Muscle biopsies, blood samples, countermovement jumps, and perception of muscle soreness were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Alternatively, other time-course analyses have observed CK levels peaking at 48 h postgame (Ispirlidis et al, 2008;Fatouros et al, 2010;Mohr et al, 2016) or have reported different deviations to these dynamics (Gunnarsson et al, 2013;Fransson et al, 2018;Bouzid et al, 2019). Observed peak values are highly heterogeneous with some authors reporting 2-4fold increases (Rampinini et al, 2011;Gunnarsson et al, 2013;Bouzid et al, 2018;Fransson et al, 2018;Daab et al, 2021;Wiig et al, 2022) while others have documented more drastic increases in circulating CK levels compared to pre-match values (Ispirlidis et al, 2008;Fatouros et al, 2010;Mohr et al, 2016). Factors such as previous exposure to intensive exercise might lead to lower elevations in CK levels resulting from increased enzyme clearance (Hyatt and Clarkson, 1998).…”
Section: Biomarkers Of Exercise-induced Muscle Damagementioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, other time-course analyses have observed CK levels peaking at 48 h postgame (Ispirlidis et al, 2008;Fatouros et al, 2010;Mohr et al, 2016) or have reported different deviations to these dynamics (Gunnarsson et al, 2013;Fransson et al, 2018;Bouzid et al, 2019). Observed peak values are highly heterogeneous with some authors reporting 2-4fold increases (Rampinini et al, 2011;Gunnarsson et al, 2013;Bouzid et al, 2018;Fransson et al, 2018;Daab et al, 2021;Wiig et al, 2022) while others have documented more drastic increases in circulating CK levels compared to pre-match values (Ispirlidis et al, 2008;Fatouros et al, 2010;Mohr et al, 2016). Factors such as previous exposure to intensive exercise might lead to lower elevations in CK levels resulting from increased enzyme clearance (Hyatt and Clarkson, 1998).…”
Section: Biomarkers Of Exercise-induced Muscle Damagementioning
confidence: 99%
“…Several studies have explored the impact of football match-play on blood CK levels of male players at different time points. Accordingly, CK levels have been reported to peak at 24 h postgame ( Rampinini et al, 2011 ; Silva et al, 2013 ; Bouzid et al, 2019 ; Wiig et al, 2022 ) and gradually decrease throughout the recovery period, with elevated CK levels persisting up to 48–72 h after the match or match simulation ( Ascensao et al, 2008 ; Rampinini et al, 2011 ; Silva et al, 2013 ; Daab et al, 2021 ; Wiig et al, 2022 ). Alternatively, other time-course analyses have observed CK levels peaking at 48 h postgame ( Ispirlidis et al, 2008 ; Fatouros et al, 2010 ; Mohr et al, 2016 ) or have reported different deviations to these dynamics ( Gunnarsson et al, 2013 ; Fransson et al, 2018 ; Bouzid et al, 2019 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional parameters are used by several authors as an indirect method to evaluate EIMD [29,[52][53][54][55]. There are many options commonly incorporated into EIMD studies that can be accessible to coaches and fitness instructors [22,26,29,[52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%